Diversity and Composition of Sulfate-Reducing Microbial Communities Based on Genomic DNA and RNA Transcription in Production Water of High Temperature and Corrosive Oil Reservoir - Li, Xiao-Xiao; Liu, Jin-Feng; Zhou, Lei; Mbadinga, Serge M.; Yang, Shi-Zhong; Gu, Ji-Dong; Mu, Bo-Zhong (Frontiers in Microbiology, 2017)
Deep subsurface petroleum reservoir ecosystems harbor a high diversity of microorganisms, and microbial influenced corrosion (MIC) is a major problem for the petroleum industry. Here we used high-throughput sequencing to explore the microbial communities based on genomic 16S rDNA and metabolically active 16S rRNA analyses of production water samples with different extents of corrosion from a high-temperature oil reservoir. Results showed that Desulfotignum and Roseovarius were the most abundant genera in both genomic and active bacterial communities of all the samples. Both genomic and active archaeal communities were mainly composed of Archaeoglobus and Methanolobus. Within both bacteria and archaea, the active and genomic communities were compositionally distinct from one another across the different oil wells (bacteria p = 0.002; archaea p = 0.01). In addition, the sulfate-reducing microorganisms (SRM) were specifically assessed by Sanger sequencing of functional genes aprA and dsrA encoding the enzymes adenosine-5'-phosphosulphate reductase (APS) and dissimilatory sulfite reductase, respectively. Functional gene analysis indicated that potentially active Archaeoglobus, Desulfotignum, Desulfovibrio and Thermodesulforhabdus were frequently detected, with Archaeoglobus as the most abundant and active sulfate-reducing group. Canonical correspondence analysis revealed that the SRM communities in petroleum reservoir system were closely related to pH of the production water and sulfate concentration. This study highlights the importance of distinguishing the metabolically active microorganisms from the genomic community and extends our knowledge on the active SRM communities in corrosive petroleum reservoirs.